2013
DOI: 10.1063/1.4789021
|View full text |Cite
|
Sign up to set email alerts
|

The modification of Schottky barrier height of Au/p-Si Schottky devices by perylene-diimide

Abstract: Perylene-diimide (PDI) thin film was fabricated by spin coating method on p-Si single-crystal substrate to prepare Au/PDI/p-Si Schottky device. The electrical properties of the Au/PDI/p-Si Schottky device were investigated by current-voltage (I–V) measurements in the temperature range 80–300 K and room temperature capacitance-voltage (C–V) measurement. Results showed a rectification behavior. Junction parameters such as ideality factor (n), barrier height (ϕB0), series resistance (Rs) interface state density (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…This value is quite higher than 0.34 of conventional Au/p-Si Schottky diodes [35] and higher than 0.58 of Au/Perylene-diimide/p-Si [39], 0.41 of Au/strontium titanate/p-Si [40] and 0.68 of Au/Poly(4-vinyl phenol)/p-Si MIS structures [41] reported in literature. On the other hand, this value is also higher than metal/DLC/pSi Schottky diodes obtained by Gupta et al [28].…”
Section: Analysis Of Current-voltage Characteristics Of Au/dlc/p-si Mmentioning
confidence: 55%
“…This value is quite higher than 0.34 of conventional Au/p-Si Schottky diodes [35] and higher than 0.58 of Au/Perylene-diimide/p-Si [39], 0.41 of Au/strontium titanate/p-Si [40] and 0.68 of Au/Poly(4-vinyl phenol)/p-Si MIS structures [41] reported in literature. On the other hand, this value is also higher than metal/DLC/pSi Schottky diodes obtained by Gupta et al [28].…”
Section: Analysis Of Current-voltage Characteristics Of Au/dlc/p-si Mmentioning
confidence: 55%
“…It was found that the value of the leakage current density for the Pc layer inserted devices varies between 2.29 × 10 −7 A/cm 2 and 6.56 × 10 −7 A/cm 2 , while the observed leakage current density was 1.38 × 10 −4 A/cm 2 for Ag/p-Si structure. It should be mentioned here that the observed level of leakage current density is significantly low when compared with the reported values with similar structure such as Au/PDI/p-Si [23] and Al/DNA/p-Si [24] Schottky devices. This findings clearly show that the main performance parameters of a SBD such as rectification ratio and leakage current can be improved by modifying p-type silicon surface with 2(3),9(10), 16(17) Various models, such as Fowler-Nordheim tunneling, Poole-Frenkel emission, and Ohmic and space charge limited (SCL) current, have widely been used to understand the nature of the charge transport through an organic thin film [25][26][27].…”
Section: Characterization Of Sbdsmentioning
confidence: 66%
“…T is the absolute temperature, A* ¼ 4pqm*k 2 h 3 is Richardson's constant and the value is 120 A cm À2 K À2 for n-type Si. 22 The ideality factor and barrier height of the Schottky barrier diodes are describe the deviation of the experimental temperature dependent I-V data is expressed as: 23,24 Fig. 4 shows the semi-logarithmic forward and reverse bias I-V characteristics of the Au/PH1000/n-Si and Au/HTL Solar/n-Si SBDs in the temperature ranging from 290 K to 380 K. From intercept and slope of ln I vs. V plot at each temperature gives the f b0 and n respectively.…”
Section: Electrical Characterizationmentioning
confidence: 99%